PENGGUNAAN ISTILAH BERBAHASA ARAB PADA KOMUNITAS PERGERAKAN ISLAM DI KOTA SEMARANG: TINJAUAN SOSIOPRAGMATIK - Retno Purnama Irawati (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2014)
The Arabic terms usage problems in Islamic Movement Community are interested to be explored by the researchers because the linguistic situation in Islamic Movement Community is enough unique if it is compared with the linguistic situation in another social community. It is necessary to be explored by deep doing about the linguistic behavior that is related to registers and speech acts, the linguistic interaction patterns in what context, to whom, when, what for and where, which them to be done by spoken. The main problems in this study are register and speech act in Arabic terms applied in Islamic Movement Community and their motivation in employing Arabic terms in doing communication in Islamic Movement Community. There were some registers and speech acts in Arabic terms applied in Islamic Movement Community found as follows: locution speech act, illocution speech act, representative speech act, comissive speech act, directive speech act. Expressive and declarative speech act were not found in their speech act. To get data about their motivation and Arabic terms applied context in doing communication in Islamic Movement Community used questionnaire. There were 150 questionnaires given to respondents and 95 questionnaire that could be taken.